Motivation and Perception of Students in Direct Command Teaching Styles and Problem-Solving in Physical Education - Corrales-Perea, Ángela; Espada, María (Revista Electrónica Educare, 2022)
Objective. To analyze motivation and development channels according to the different teaching styles used through the intervention of the Rhythm and Music Support Didactic Unit. Method. It is a quasi-experimental and quantitative design, and 53 students participated in this study. They were divided into two groups; one group received an intervention based on the direct command teaching style and problem-solving technique, in this order, while the second group did it the other way round. The Rhythm and Musical Support Didactic Unit consists of 4 sessions of 50 minutes each one. Results. The information was collected through two questionnaires and analyzed through the statistical program IBM-SPSS version 24 for Windows. After the intervention, there were no improvements in the BPNES, while the cognitive, physical, and emotional factors presented higher scores through the problem-solving teaching style. Conclusions. The problem-solving teaching style shows more development in the relationship between classmates, surpassing the direct command teaching style. Regarding the gender variable, it is reflected that women who started with the problem-solving style have a higher level of autonomy.